Literatur Review Gaya Kepemimpinan Partisipatif Kepala Sekolah , Keterlibatan dan Efektivitas Kinerja Guru di Sekolah - Aan Prastiyo; Ima Widiyanah; Kaniati Amalia; Muhammad Nursalim; Amrozi Khamidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of the principal's participatory leadership style on the involvement and effectiveness of teacher performance in schools. There are several types of leadership styles, one of which is participatory leadership style. This leadership style provides space for subordinates to participate more in making a decision. Subordinates' opinions are listened to, of course, if they provide new views and are in accordance with the goals to be achieved. The relationship between superiors and subordinates is very friendly and warm and there is no authoritarian atmosphere. Teacher involvement is an important aspect that includes various dimensions, from active participation in work to roles in decision-making in schools. Factors that influence the effectiveness of teacher performance are ability, motivation, environmental conditions and opportunities. This study uses a literature review approach. The conclusion is that various previous studies strengthen this finding, showing the influence of the principal's participatory leadership style on the involvement and effectiveness of teacher performance in the school environment. Keywords: Teacher Performance Effectiveness, Participatory Leadership Style, Involvement